ANALISIS KEPUASAN WISATAWAN MANCANEGARA TERHADAP KUALITAS PELAYANAN PARIWISATA - Wirajaya, Yessy (JURNAL MANAJEMEN DAN AKUNTANSI, 2013)
The analysis of the South-East Moluccas development plan 2008-2013 shows that one of the problems in developing tourism is the low quality of tourism services. This research will provide an analysis of services quality according to five dimensions; which include tangibility, reliability, responsiveness, assurance, and empathy. This research also aims to analyze the satisfaction of tourists toward services quality tourism industry in South-East Moluccas. This research employs qualitative approach, cross sectional descriptive study. The subject of this research is four tourists who had their vacation in South-East Moluccas and experienced the tourism service and facilities. The data were collected by interviewing the subjects and recording the events, then the results was analyzed by using the model of Miles and Huberman. Most the tourists state that they are motivated to visit South-East Moluccas after reading other tourists recommendation in website (online word-of-mouth) most of these tourists value the beauty of nature and relax atmosphere of the South-East Moluccas. The result of this research also reveals areas of improvement amongst five service quality dimensions. Keywords: service quality, satisfaction, cross sectional, tourism.